Are members of multidisciplinary teams in breast cancer aware of each other's informational roles?. Issue 2 (1st June 2001) - Jenkins, V A; Fallowfield, L J; Poole, K
Abstract : Aim —To conduct a commissioned survey of multidisciplinary breast team members' expectations of their own and each other's roles in providing different kinds of information to women with breast cancer. Design —Questionnaire based survey. Setting and participants —Health professionals from five multidisciplinary breast care centres within a Sussex health authority. Main outcome measures —Interdisciplinary awareness of informational roles played by different team members. Results and conclusions —The results of the team survey suggest that, in most cases, health professionals fulfilled the roles expected of them by the team, with two or three individuals identified as the main providers of information for each topic. However, many more professionals were involved in major discussions without the team's knowledge. The professional consistently playing a major "unseen" role was the breast nurse specialist.